Nanos and Pumilio have critical roles in the development and function of Drosophila germline stem cells. - Forbes, A.; Lehmann, R. (Development, 1998)
The zinc-finger protein Nanos and the RNA-binding protein Pumilio act together to repress the translation of maternal hunchback RNA in the posterior of the Drosophila embryo, thereby allowing abdomen formation. nanos RNA is localized to the posterior pole during oogenesis and the posteriorly synthesized Nanos protein is sequestered into the germ cells as they form in the embryo. This maternally provided Nanos protein is present in germ cells throughout embryogenesis. Here we show that maternally deposited Nanos protein is essential for germ cell migration. Lack of zygotic activity of nanos and pumilio has a dramatic effect on germline development of homozygous females. Given the coordinate function of nanos and pumilio in embryonic patterning, we analyzed the role of these genes in oogenesis. We find that both genes act in the germline. Although the nanos and pumilio ovarian phenotypes have similarities and both genes ultimately affect germline stem cell development, the focus of these phenotypes appears to be different. While pumilio mutant ovaries fail to maintain stem cells and all germline cells differentiate into egg chambers, the focus of nanos function seems to lie in the differentiation of the stem cell progeny, the cystoblast. Consistent with the model that nanos and pumilio have different phenotypic foci during oogenesis, we detect high levels of Pumilio protein in the germline stem cells and high levels of Nanos in the dividing cystoblasts. We therefore suggest that, in contrast to embryonic patterning, Nanos and Pumilio may interact with different partners in the germline.